A framework for conceiving of job-related affective wellbeing - Peter J. Hosie; Peter P. Sevastos (Management Revue, 2010)
Beginning with the nature of happiness, the philosophical roots of job-related affect are explored to inform contemporary understandings of the phenomenon. Various disciplines, theories, models and schools of thought are contextualised and related to job-related affective wellbeing. Seminal constructs of affective wellbeing are identified, along with issues involved in developing an integrated model of affective wellbeing in the workplace. A synthesis of the literature is given using a tripartite heuristic framework comprising categories of Dispositional, Activity and Telic. Each category explains the tenets of the most influential theories and debates their veracity. Finally, the key theoretical developments are integrated to provide linkages between the conceptual bases of these constructs.
Keywords: 650; job; affective wellbeing; intrinsic job satisfaction; dispositional; activity; telic